Critérios de imputação de crimes omissivos impróprios a dirigentes empresariais: uma análise doutrinária e jurisprudencial - Bazzi, Matheus Amélio de Souza (Universidade do Vale do Rio dos Sinos, 2025)
This dissertation investigates the complex criteria for imputing improper omission crimes to corporate executives, analyzing the doctrine and jurisprudence of the Superior Court of Justice (STJ) and the Supreme Federal Court (STF). It`s central problem questions how and under what circumstances corporate executives can be held criminally liable for offenses committed by their subordinates through improper omission. The hypothesis points to a lack of clarity and legal certainty, which can hinder entrepreneurial activity. The study focuses on "commission by omission" and the essential "guarantor position," exploring theories that underpin the duty to act, formal and material ones, as well as debating the complexity of subjective imputation in fragmented corporate structures. Thus, it investigates the view of the company as a "source of danger" and its executives as guarantors, as well as the implications of task delegation. In this regard, the analysis proceeds to evaluate effective criminal compliance programs and their contribution in the face of presented risks, outlining their fundamental pillars. Following the theoretical investigation, a jurisprudential analysis of the STJ and STF is conducted, which proves revealing for the research hypothesis.
Keywords: Direito penal econômico; Dirigentes de empresas; Responsabilidade penal; Economic criminal law; Corporate executives; Criminal liability; Improper omission; ACCNPQ::Ciências Sociais Aplicadas::Direito